BEYOND TRADITIONAL PRACTICES: INVESTIGATING CUTTING-EDGE E-PROCUREMENT INITIATIVES FOR CONTRACTOR SELECTION IN PUNJAB PAKISTAN CONSTRUCTION INDUSTRY – A CASE STUDY OF PUBLIC SECTOR CLIENTS - Rana Farhan Ali; Memon, Nafees Ahmed; Pathan, Ashfaque Ahmed (Tropical Scientific Journal, 2023)
Objective: This research is carried out to assess the current status of e-procurement initiatives and the barriers the Pakistani construction industry faces in implementing e-procurement. The research gap in this study pertains to the lack of comprehensive research on e-procurement operations, particularly within the construction industry in Pakistan. This study is to examine and assess the existing e-procurement initiatives in the construction industry, focusing on their implementation scope and the degree of acceptability of digital technologies. The aim is to address the existing knowledge gap in this area and examine the viewpoints and attitudes of key stakeholders in relation to the implementation of e-procurement. Additionally, it seeks to identify barriers that are particular to the context and hinder the successful implementation of e-procurement. This study aims to assess procurement sector employees' familiarity with the e-procurement system. Research Method: Through a comprehensive investigation of the identified barriers, this study sheds light on the issues impeding the successful deployment of e-procurement practices. Using survey data collected from public sector employees, the study presents its findings through a variety of charts and analyses. Findings: The results reveal that 39% of respondents were fully aware of e-procurement systems, while 61% had a limited understanding. To improve their knowledge in this area, more awareness and training are needed. Electronic procurement has used e-tendering, e-sourcing, and e-informing less. With 36% use, SAP Ariba was the most popular e-procurement software. Khareed.pk had the lowest usage, at 6%. Respondents utilized purchase order and vendor management software. Electronic bidding has become the standard way of submitting proposals, signaling a shift towards digital procurement. 56% of respondents said e-procurement worked. 36% found it extremely effective. E-procurement was doubted or difficult for 8%. This study offers important insights into the implementation and utilization of e-procurement initiatives in Pakistan's construction industry. Originality: This study's findings can serve as a valuable resource for policymakers, construction firms, and other relevant parties interested in advancing e-procurement practises in Pakistan.